2001
DOI: 10.1159/000049511
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-17 and the Neutrophil in Asthma

Abstract: Recent clinical evidence shows that acute, severe exacerbations of asthma are associated with recruitment and activation of neutrophils in the airways. There is also experimental evidence from rodents that T-lymphocytes are involved in the recruitment of neutrophils following allergen challenge in sensitised airways. This review addresses the potential role of neutrophils and the cytokine interleukin-17 (IL-17) in severe asthma. IL-17 is produced and released as a free protein from T-lymphocytes of the memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
105
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 41 publications
3
105
1
2
Order By: Relevance
“…Other potential roles of IL-17A in asthmatic airways might include the stimulation of mucus cell differentiation 25,41 and induction of chemokine and nitric oxide release. 22,23,30,42 Our study suggests that coexistence of T H 2 cytokines and IL-17A might have a significant effect on the pathogenesis of asthma by positively modulating the existing T (Fig 6, B and C). However, STAT6 nuclear translocation and IL-19 promoter binding were similar in IL-13-and IL-13/IL-17A-treated cells, despite the fact that IL-17A/IL-13-cotreated cells express much higher IL-19 compared with IL-13 alone.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Other potential roles of IL-17A in asthmatic airways might include the stimulation of mucus cell differentiation 25,41 and induction of chemokine and nitric oxide release. 22,23,30,42 Our study suggests that coexistence of T H 2 cytokines and IL-17A might have a significant effect on the pathogenesis of asthma by positively modulating the existing T (Fig 6, B and C). However, STAT6 nuclear translocation and IL-19 promoter binding were similar in IL-13-and IL-13/IL-17A-treated cells, despite the fact that IL-17A/IL-13-cotreated cells express much higher IL-19 compared with IL-13 alone.…”
Section: Discussionmentioning
confidence: 70%
“…This is the first demonstration that a T H 2 cytokine can coordinate with a proinflammatory cytokine, such as IL-17A, to potentiate a T H 2 response. 11,18,[28][29][30][31] This discovery emphasizes the uniqueness of epithelia-derived IL-19 in allergic diseases and suggests important roles for IL-13 and IL-17A in IL-19 regulation. [32][33][34] We hypothesize that airway epithelial IL-19 is induced by IL-17A and T H 2 cytokines, mainly IL-13, to further potentiate a T H 2-dominant response in a positive feedback manner in the context of allergic airway diseases, such as asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is worth mentioning here that work in human subjects both has suggested that neutrophils may be potentially important contributors to airway pathology in certain subsets of patients with asthma, [41][42][43][44][45][46][47][48] and has identified IL-17 expression in the lungs of some subjects with this disorder. 32,[49][50][51][52][53] Therefore, it will be of interest to attempt to investigate whether the mechanisms that contribute to the mast cell-dependent enhancement of IL-17-dependent airway neutrophilia that have been revealed in our analyses of OTII mice have any bearing on the regulation of neutrophil recruitment that can occur in human asthma.…”
Section: Discussionmentioning
confidence: 99%